Soft tissue angiofibroma: Clinicopathologic, immunohistochemical and molecular analysis of 14 cases. Issue 10 (25th July 2017) - Bekers, Elise M; Groenen, Patricia JTA; Verdijk, Marian AJ; Raaijmakers‐van Geloof, Winny L; Roepman, Paul; Vink, Robert; Gilhuijs, Nathalie DB; van Gorp, Joost M; Bovée, Judith VMG; Creytens, David H; Flanagan, Adrienne M; Suurmeijer, Albert JH; et al.
Abstract: Soft tissue angiofibroma is rare and has characteristic histomorphological and genetic features. For diagnostic purposes, there are no specific antibodies available. Fourteen lesions (6 females, 8 males; age range 7‐67 years) of the lower extremities (12) and trunk (2) were investigated by immunohistochemistry, including for the first time NCOA2. NCOA2 was also tested in a control group of other spindle cell lesions. The known fusion‐genes ( AHRR‐NCOA2 and GTF2I‐NCOA2 ) were examined using RT‐PCR in order to evaluate their diagnostic value. Cases in which no fusion gene was detected were additionally analysed by RNA sequencing. All cases tested showed nuclear expression of NCOA2. However, this was not specific since other spindle cell neoplasms also expressed this marker in a high percentage of cases. Other variably positive markers were EMA, SMA, desmin and CD34. STAT6 was negative in the cases tested. By RT‐PCR for the most frequently observed fusions, an AHRR‐NCOA2 fusion transcript was found in 9/14 cases. GTF2I‐NCOA2 was not detected in the remaining cases ( n = 3). RNA sequencing revealed three additional positive cases; two harbored a AHRR‐NCOA2 fusion and one case a novel GAB1‐ABL1 fusion. Two cases failed molecular analysis due to poor RNA quality. In conclusion, the AHRR‐NCOA2 fusion is a frequent finding in soft tissue angiofibroma, while GTF2I‐NCOA2 seems to be a rare genetic event. For the first time, we report a GAB1‐ABL1 fusion in a soft tissue angiofibroma of a child. Nuclear expression of NCOA2 is not discriminating when compared with other spindle cell neoplasms.